2005
DOI: 10.1158/0008-5472.can-05-1886
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles Associated with Treatment Response in Oligodendrogliomas

Abstract: Oligodendrogliomas are a specific subtype of brain tumor of which the majority responds favorably to chemotherapy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 51 publications
7
78
0
Order By: Relevance
“…Two previous studies have reported similar comparisons of genotype and gene expression in oligodendroglial tumors [7,25]. French et al reported 60 genes associated with 1p/19q loss and Mukasa et al reported 209 genes associated with 1p loss; only a few of the genes identified were differentially expressed in this study.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Two previous studies have reported similar comparisons of genotype and gene expression in oligodendroglial tumors [7,25]. French et al reported 60 genes associated with 1p/19q loss and Mukasa et al reported 209 genes associated with 1p loss; only a few of the genes identified were differentially expressed in this study.…”
Section: Discussionsupporting
confidence: 72%
“…Of these, neuronal intermediate filament protein, alphainternexin (INA) and the scaffold protein IQGAP1 have been investigated in other glioma studies [6,7], while the steroid/thyroid hormone receptor, NR2F2 and the transforming growth factor beta inhibiting protein, TGIF1, represent novel findings of differential expression in gliomas. Three genes on 1p, down-regulated approximately two-fold, are of note.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Refs. 43-50 were reanalyzed to show expression level of Emi1 in normal brain, glioblastoma, oligodendroglioma, anaplastic oligodendroglioma, astrocytoma, head and neck cancer, breast cancer, pancreatic ductal adenocarcinoma, cervical cancer, transitional cell carcinoma, and adult male germ cell tumor (43)(44)(45)(46)(47)(48)(49)(50). N, normal tissues; T, tumor tissues.…”
Section: Emi1 Knockdown Enhances the Induction Of Apoptosis By Doxorumentioning
confidence: 99%
“…Microsatellites were amplified by PCR on 20 nanogram genomic DNA, using a fluorescently labeled forward primer and a reversed primer. Allelic losses were statistically determined as described and scored by two independent researchers (French et al, 2005). TP53 (NM_000546.4, GI:187830767) status was determined in 169 samples.…”
Section: Samplesmentioning
confidence: 99%